Punitive Damages Under the New Chinese Civil Code – A Critical and Comparative Analysis - Janssen, André; Wang, Jia (Asia Pacific Law Review, 2025)
Punitive damages have their roots in the common law system. Recently, punitive damages have been increasingly discussed also in non-common law jurisdictions. This Article scrutinizes whether it is viable for a jurisdiction with a civilian legal system to adopt punitive damages in the realm of tort law. It is argued that societal development has brought unprecedented challenges to tort law where merely compensatory damages can no longer provide sufficient remedies to victims. We conduct research mainly from the perspective of China, which has been very progressive in introducing punitive damages into various areas of private law in the past decades and recently codified it in its new Chinese Civil Code. The discussion of Chinese law is proceeded with a comparison with the German law, which is also a civilian legal system that used to have a great influence on the making of Chinese law. We find that the German private law put much emphasis on disgorgement damages, while the Chinese legislator put his trust in punitive damages. German disgorgement damages and Chinese punitive damages focus both on the avoidance of efficient breaches of ubiquitous individual legal rights, such as personality rights or intellectual property rights, but the Chinese legislator makes punitive damages also available in several other legal situations. We provide recommendations for the future implementation of the Chinese punitive damages law in order to maintain a balance between efficient protection for claimants and sanctions on wrongdoers.
EPrint Processing Status: Full text deposited in DRO